2006
DOI: 10.1515/cclm.2006.149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical markers of atherosclerosis in young and elderly Japanese adults

Abstract: These results demonstrate basic profiles of atherosclerosis markers in young and elderly Japanese adults. Further study is needed to evaluate measures developed for application in early adulthood to prevent atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
0
34
1
Order By: Relevance
“…Durga et al (31) recently reviewed the relationship between hyperhomocysteinemia and CIMT and concluded that this association is often weak or absent in the general population. Furthermore, we reported that CIMT was significantly correlated with HCY in young and elderly women, but not in men (24). Conversely, the present study showed that CIMT was significantly increased in the highest quintile of tHCY levels, after adjusting CIMT for age and sex.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Durga et al (31) recently reviewed the relationship between hyperhomocysteinemia and CIMT and concluded that this association is often weak or absent in the general population. Furthermore, we reported that CIMT was significantly correlated with HCY in young and elderly women, but not in men (24). Conversely, the present study showed that CIMT was significantly increased in the highest quintile of tHCY levels, after adjusting CIMT for age and sex.…”
Section: Discussioncontrasting
confidence: 87%
“…Measurement of CIMT by ultrasonography of the left and right carotid arteries was performed using a LOGIC Book XP system with a 10-MHz linear-array transducer (GE Medical Systems, Milwaukee, WI, USA). A detailed protocol has been described elsewhere (24). CAVI was recorded using a VaseraVS-1000 vascular screening system (Fukuda Denshi, Tokyo, Japan) with the subject resting in a supine position.…”
Section: Methodsmentioning
confidence: 99%
“…10-MHz transducer, GE Healthcare, Milwaukee, WI, USA). The protocol they used has been described in detail elsewhere [17]. The values of right and left CIMT without measurement of plaque were calculated and the higher CIMT value was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed protocol has been described elsewhere. 18 Averages of left and right CIMT were calculated and used in the analysis. Intra-observer variation of CIMT (N.T., n=32) was 0.91 (p<0.01), and interobserver variation (N.T.…”
Section: Measurement Of Cavi and Cimtmentioning
confidence: 99%